Glisten and Glint: The Ajay Way - Horgan, Mervyn (Critical Studies in Improvisation / Études critiques en improvisation, 2025)
Mervyn Horgan reflects on his relationship with Ajay Heble, from the start of his work at the University of Guelph to present day.